Survey of Level of Satisfaction of Rafting Tourists in Bingai River Explore Sumatra Langkat Regency North Sumatera Year 2025 - Sembiring, Robi Eykel Gantina; Ibrahim, Ibrahim; Hutagalung, Rinaldi Rahman; Sihombing, Rai Deri; Manik, Meylin Olivia Putri; Tumanggor, Muhammad Farhan; Bahri, Attila; Annur, Fausiah; Marbun, Styven Horas Parasian; Hanum, Dwi; Gressya, Iche; Sukri, Royhan (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
The purpose of this study was to determine the level of visitor satisfaction at Explore Sumatra in 2025 with the services provided by the manager. This research was conducted at the Explore Sumatra operator Sungai Bingai, Langkat Regency, North Sumatra Province. Data collection starts from January 08 - March 09, 2025. The number of samples in this study amounted to 40 people. This research is a type of descriptive research using the survey method, data collection techniques using the accidental sample method (accindental sampling). The instrument used is a questionnaire, with validity and reliability tests. To analyze the data used descriptive quantitative with percentages. The results showed that the level of visitor satisfaction with the services provided by Explore Sumatra operators was in the “Quite Satisfied” category of 55%. And the results of research based on elements, namely: (1) Attracions (“Quite Satisfied”: 57.5%), (2) Facilities (“Satisfied”: 95%), (3) Infrastructure (“Less Satisfied”: 75%), (4) Transportations (‘Satisfied’: 55%), (5) Hospitally (“Satisfied”: 50%). It can be concluded that the level of satisfaction that has been given by the manager of Explore Sumatra to visitors is in the “Quite Satisfied” category.